Critical Review of Musta in the Management of Atisara - Bagade, Subhas (International Research Journal of Ayurveda & Yoga, 2022)
Atisara (Diarrhoea) is a most common disorder of Gastrointestinal tract and is very much commonly seen in general practice. Atisara is characterized by loose watery stools and most of the time will be controlled by simple fasting (Langhana). In classics we get many more formulations for management of Atisara. Musta, Cyperus rotundus Linn belonging to Cyperaceae family is one such wonderful drug which is explained as effective in almost all types viz, Ama, Pakwa, Alpadoshaja, Madhya doshaja, Samapittaja, Pittaja, KaphajaAtisara. Here an attempt is made to review Brihatrayi to analyse mode of action, method of administration of Musta in Atisara.